(untitled) (The Pakistan Development Review, 2008)
The global export patterns are changing fast as a result of reduction in trade barriers and technological advancements that have led to gains in productivity and change in comparative advantage patterns in world economies. Asian economies such as China and India are enjoying a notable growth in changing circumstances across the world. Pakistan also has great potential for higher growth however the political threats, socioeconomic environment and lack of updated technologies are obstruction in the way of progress. Some sectors of Pakistan economy have shown a good performance in terms of production and exports. Footwear is one such industry which has increased its exports at large extent since 2003. This sector has pivotal importance in terms of providing and creating jobs, earning of foreign exchange with the help of exports and fulfilling the local consumption requirements. Both in Pakistan and around the globe, the demand for footwear is increasing. Pakistan is one of the most populous countries in the World and according to an estimate with an average population growth of 2.25 percent, about 3 million children have been born during the year 2005-06, signaling the growing demand for footwear in Pakistan. It is also estimated that about 60 percent of the World’s total consumption consists of simple footwear made entirely of non-leather materials and that for the remaining 40 percent only the upper part of the shoe is made of leather. In the manufacturing of footwear, most frequently used material consists upon leather, man-made materials, rubber / canvas / synthetic and textile along accessories. Different type of shoes are being produced by the local industry e.g. sportsmen, army, disabled persons and safety shoes for the industrial workers etc. The population of Pakistan is expected to be about 172 million in the year 2010. Keeping in view the growth in population, the growth in the demand of footwear industry is also anticipated.